A Comparative Study of SDS-PAGE, SEC-UV, and SEC-MALS in Assessing Monoclonal Antibody Aggregation - Pakalapati, Ajay; Aluru, Ranganadha Reddy; Gupta, Prateeksha; Yejju, Charita (International Journal of Pharmaceutical Investigation, 2026)
Objectives Monoclonal antibodies are prone to aggregate formation at elevated temperatures due to the disruption of their native conformation resulting in protein denaturation, disulphide linkage disruptions and eventually resulting in the loss of their key biological functions. Detection of protein aggregation is a key quality attribute which ensures biological stability, potency and dosage determination. Bulk biological manufacturing, logistics and supply chain, storage, patient delivery are the transition points of any clinical product Lifecyle. A wide variety of advanced analytical methods are used in the biopharma industry for ensuring high standard product quality and safety aspects for the product to meet its desired clinical outcome. Thermal kinetics-based studies provide an insight into molecular folding and aggregate formation as they forcibly induce protein aggregation at an accelerated pace. Forced thermal aggregation studies mimic the temperature excursion influence on the therapeutic monoclonal antibodies during their product lifecycle. Materials and Methods In the current study, we evaluated protein aggregation of IgG1 Cetuximab mAb sample using advanced analytical techniques including Sodium dodecyl Sulphate-Poly Acryl Amide Gel Electrophoresis (SDS-PAGE), Size Exclusion Chromatography (SEC), and multi-angle light Scattering (SEC-MALS), and cetuximab sample was subjected to thermal kinetics to evaluate aggregation at an elevated temperature of 70º centigrade at multiple time points T0, T1 and T2 etc., Results and Discussion Resulting thermal aggregation products are analysed using traditional SDS PAGE and advanced SEC-UV and SEC-MALS methods. We observed dimer formation because of protein aggregation in a time of 30 min at 70ºC. Further increment in temperature resulted in an overall increase in the quantity of the dimer product and additionally resulted in the formation of higher order trimer species. Conclusion Analytical results from three different platforms have indicated protein aggregation. SDS-PAGE is a simple cost-effective tool for preliminary aggregation assessment. Advanced techniques provide a robust, high-throughput and accurate quantified results for the estimation of protein aggregates.
Keywords: SDS-PAGE; SEC-UV; SEC-MALS; Monoclonal Antibody